Fabrication of stimuli responsive hyaluronic acid-based nanoparticles for cancer treatment - Phua, Fiona Soo Zeng (2019)
Non-selective cancer treatment causes low treatment efficacy and severe side effects in patients. Considering the current problem in oncology such as high systemic toxicity of chemodrug and poor efficiency of photodynamic therapy, the focus of this thesis is to design, fabricate and characterize hyaluronic acid based nanocarriers for stimuli-responsive targeted cancer therapy by supramolecular means. Various hyaluronic acid-based nano-sized systems have been designed and investigated for cancer treatment. Hyaluronic acid-based nanocarriers have numerous advantages such as its biodegradability and non-immunogenetic. Multiple functional groups on the hyaluronic acid also allows for facile modifications to allow for greater functionality. Formation of micelles, direct conjugation and formation of nanogels could be achieved. Hyaluronic acid could also target overly expressed receptors on cancer cells. Different hyaluronic acid-based nanocarriers will be explored in this thesis to prove its versatility as a polymer for delivery of cancer therapeutic agent. To further increase selectivity of treatment, stimuli-responsive groups will be incorporated. To better control the amount of therapeutic agents, supramolecular chemistry will be harnessed. Chapter 1 describes the background of cancer, treatment modalities and current research using nanocarrier, and more specifically, using hyaluronic acid as the polymer for drug delivery of therapeutic agents. It also describes some current development in stimuli responsive drug delivery system and lastly introduced supramolecular chemistry as a mean for nanoparticle fabrication. In Chapter 2, our primary objective was to design a hyaluronic acid-based nanocarrier based on self-assembly after formation of inclusion complex between the cyclodextrin-modified hyaluronic acid and adamantane-modified camptothecin drug and photosensitizers. The nanocarrier HA-aPS-aCPT was able to target the overly expressed CD44 receptors on cancer cells. Furthermore, upon internalization, light irradiation was applied so that the photosensitizers produced reactive oxygen species. This was used for photodynamic therapy as well as the release of the caged prodrug via the reaction with the reactive oxygen species responsive linker. This resulted in cascaded release of active chemodrug. The system was applied on mice model and had shown to inhibit tumour growth. Beside using hyaluronic acid polymer for encapsulation of drugs and photosensitizers, hyaluronic acid polymers could be used for direct conjugation with proteins or enzymes that can improve therapeutic outcome. Hence, in Chapter 3, we explored the possibility of direct conjugation of hyaluronic acid onto enzyme catalase. Direct conjugation of catalase increased its stability in the presence of proteinase K, which was essential for long term blood circulation in in vivo system. Photosensitizers was loaded into the nanocarrier by formation of inclusion complex of cyclodextrin modified on hyaluronic acid and the adamantane-modified chlorin e6 to form HA-CAT@aCe6 NPs. Modification with catalase in the nanocarrier could relieve hypoxia in cells. Because of the presence of hyaluronic acid, HA-CAT@aCe6 NPs was able to target CD44+ cells selectively. Upon irradiation of light, HA-CAT@aCe6 NPs inhibited the tumour growth in mice model as compared to hyaluronic acid with photosensitizers alone. This shows that modification of hyaluronic acid with enzymes were effective in preserving its activity and improve its biodistribution for application. Beside using catalase to overcome the hypoxia in cells, another approach is to use prodrug that is responsive to hypoxia environment for release of drug. In Chapter 4, glucose oxidase, an enzyme that was able to convert glucose and oxygen to hydrogen peroxide was encapsulated in hyaluronic acid-based nanogels. Tirapazamine, a hypoxia-responsive drug was co-loaded into the HA nanogel to give HA@aCe6@GOD-TPZ. aCe6 in this case was the hydrophobic component for self-assembly of the HA nanogel and to perform imaging. Glucose oxidase can deplete the oxygen level in cells to release the prodrug. HA@aCe6@GOD-TPZ was able to accumulate selectively in CD44+ cells. The NPs was shown to be able to exhibit greater cytotoxicity under hypoxic condition than HA@aCe6@GOD and TPZ alone. Chapter 5 concludes the usage of hyaluronic acid as a polymeric nanocarrier in terms of formation of micelle, nanocarrier and nanogels. New insights for future research on nanocarrier for treatment of cancer was also provided.